The positive conception of secularism as a negation of the very concept of secularism - Blando, Giovanni (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
This article critically analyzes the concept of ‘positive’ or ‘healthy secularism’ supported by the church hierarchy underlying its confusion with the sociological concept of secularization and its incompatibility with two fundamental values of the Constitutional State: freedom and equal concern and respect.